The Effects Of Rasagiline On Cognitive Deficits in Parkinson's Disease Patients Without Dementia: A Randomized, Double-Blind, Placebo-Controlled, Multicenter Study - Hanağası, Haşmet Ayhan; Gürvit, Hakan; Ünsalan, Pınar; Horozoğlu, Hilal; Tuncer, Neşe; Feyzioğlu, Aynur; Günal, Dilek İnce; Yener, Görsev G.; Çakmur, Raif; Şahin, Hüseyin Alparslan; Emre, Murat (Wiley-Blackwell, Commerce Place, 350 Main St, Malden 02148, Ma Usa, 2011)
Cognitive impairment can occur at all stages of Parkinson's disease. Rasagiline is a selective monoamine oxidase type-B inhibitor that enhances central dopaminergic transmission. Dopamine is thought to be involved in certain cognitive processes such as working memory. We assessed the effects of rasagiline on cognitive deficits in cognitively impaired, nondemented patients with Parkinson's disease. This was a randomized, double-blind, placebo-controlled prospective study. Patients with Parkinson's disease receiving stable dopaminergic treatment were assigned to receive rasagiline 1 mg/day or placebo for 3 months. Patients were eligible if they had impairment in 2 of 4 cognitive domains (attention, executive functions, memory, visuospatial functions) in the screening neuropsychological tests, yet did not fulfill criteria for Parkinson's disease dementia. Fifty-five patients were randomized; 48 patients completed the study. Patients in the rasagiline group showed significant improvement in digit span backward compared with the placebo group (P = .04), with trends favoring rasagiline in digit span total and digit-ordering tests. Verbal fluency total score showed a significant difference in favor of rasagiline (P = .038), with trends favoring rasagiline in semantic fluency test and Stroop spontaneous corrections. The composite cognitive domain Z scores revealed a significant difference in favor of rasagiline compared with placebo in the attentional Z score (P < .005). There were no significant differences between the 2 groups in the other cognitive tests or cognitive domain Z scores. The monoamine oxidase type-B inhibitor rasagiline may exert beneficial effects on certain aspects of attention and executive functions in nondemented patients with Parkinson's disease with cognitive impairment. (C)2011 Movement Disorder Society
Keywords: Parkinson's disease; cognitive impairment; treatment; rasagiline; attention; dopaminergic modulation; working-memory; dysfunction; interference; performance; levodopa; cortex; cohort; onset; Parkinson hastalığı; Kognitif bozukluk; tedavi; rasagilin; dikkat; dopaminerjik modülasyonu; çalışan bellek; fonksiyon bozukluğu; girişim; performans; levodopa; korteks; kohort; başlangıç